(untitled) (The Agriculturists, 2013)
An investigation was conducted to isolate and identify the causal agent of infectious coryza (IC) with pathogenesis study by local isolate of Avibacterium paragallinarum in chicks in Bangladesh. One isolate of A. paragallinarum was used to study the experimental pathogenesis. For this, 14 days old 24 chicks were grouped into two (A and B) and each group contained 12 birds. Chicks of group A were inoculated with 1ml of 2 days old nutrient broth and were kept as control group while group B were inoculated with 1 ml of 2 days old culture broth of A. paragallinarum. To study the pathology, 4 birds from each group were sacrificed on day 3, 5 and 7 of post inoculation. Sacrificed birds of group A did not reveal any clinical sign and lesion. Chicks of group B showed mild nasal discharge, conjunctivitis, depression and inability to move. The gross lesions of the chicks of group B included mucous in nasal passage, conjunctivitis, swelling of sinuses and face and congested lungs. The microscopic lesions of the chicks of this group were acanthosis and congested blood vessels of nasal passage, pneumonic lesion of lung, focal hepatitis of liver and fatty change and lipid nodules in macrophages of heart which were progressively prominent on day 7 of bacterial inoculation. A. paragallinarum was reisolated from day 7 of post inoculation (PI) from nasal passage of chicks in which lesions were prominent. The proposed experimental pathogenesis was after intranasal inoculation with A. paragallinarum, rhinitis developed, bacteria entered into blood, reached different organs producing lesions. The lesions which are discussed here (rhinitis in association with focal hepatitis, fatty change in heart with lipid granuloma, progressive pneumonic lesions) are not usually present in adult and young birds. DOI: http://dx.doi.org/10.3329/agric.v11i1.15240 The Agriculturists 2013; 11(1) 39-46